Asymmetric response of root-associated fungal communities of an arbuscular mycorrhizal grass and an ectomycorrhizal tree to their coexistence in primary succession - Knoblochová, Tereza; Kohout, Petr; Püschel, David; Doubková, Pavla; Frouz, Jan; Cajthaml, Tomáš; Kukla, Jaroslav; Vosátka, Miroslav; Rydlová, Jana (Mycorrhiza, 2017)
The arbuscular mycorrhizal (AM) grass Calamagrostis epigejos and predominantly ectomycorrhizal (EcM) tree Salix caprea co-occur at post-mining sites spontaneously colonized by vegetation. During succession, AM herbaceous vegetation is replaced by predominantly EcM woody species. To better understand the interaction of AM and EcM plants during vegetation transition, we studied the reciprocal effects of these species' coexistence on their root-associated fungi (RAF). We collected root and soil samples from three different microenvironments: stand of C. epigejos, under S. caprea canopy, and contact zone where roots of the two species interacted. RAF communities and mycorrhizal colonization were determined in sampled roots, and the soil was tested for EcM and AM inoculation potentials. Although the microenvironment significantly affected composition of the RAF communities in both plant species, the effect was greater in the case of C. epigejos RAF communities than in that of S. caprea RAF communities. The presence of S. caprea also significantly decreased AM fungal abundance in soil as well as AM colonization and richness of AM fungi in C. epigejos roots. Changes observed in the abundance and community composition of AM fungi might constitute an important factor in transition from AM-dominated to EcM-dominated vegetation during succession.
Keywords: Calamagrostis epigejos; Salix caprea; Salix; půdní mikrobiologie; mykorhiza; stromy; Poaceae; Mycorrhizae; Primary succession; Ectomycorrhiza; Czech Republic; lipnicovité; Soil Microbiology; Root-associated fungal communities; ekosystém; Česká republika; Ecosystem; Trees; Arbuscular mycorrhiza